Vitamin K2 - Vital for Health and Wellbeing 2017
DOI: 10.5772/67153
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K2 Facilitating Inter-Organ Cross-Talk

Abstract: This chapter features how vitamin K2 is instrumental in bringing about inter-organ communication, thus facilitating (a) a synthesis/secretion of the endocrine, humoral factors from various organs and (b) physiological responses to the said factors by a multitude of organ systems of the body, thus creating a 'lattice' of reciprocal regulatory loops in order to ensure endocrine homeostasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Low vitamin D levels are likely to contribute to muscle weakness and increased risk of falls in addition to increased bone fragility [61,62]. Finally, vitamin K is essential for the effective function of proteins including those involved for bone remodeling and it has been shown that in vitro vitamin K improves the proliferation and migration of primary bovine skeletal satellite cells, with potential in maintaining normal muscle function, as well as facilitating several pathways in muscle-bone crosstalk [63,64].…”
Section: Risk Factors and Pathophysiologymentioning
confidence: 99%
“…Low vitamin D levels are likely to contribute to muscle weakness and increased risk of falls in addition to increased bone fragility [61,62]. Finally, vitamin K is essential for the effective function of proteins including those involved for bone remodeling and it has been shown that in vitro vitamin K improves the proliferation and migration of primary bovine skeletal satellite cells, with potential in maintaining normal muscle function, as well as facilitating several pathways in muscle-bone crosstalk [63,64].…”
Section: Risk Factors and Pathophysiologymentioning
confidence: 99%